Hungarian Monitoring, 23 August 1989 . [Magyar rádiófigyelő], 1989. augusztus 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reports on the anniversary of the Soviet-German non-aggression pact - Report from Tallinn on human chain - Ceauşescu interview in Moscow Pravda - Polish parliament supports Mazowiecki Domestic Affairs: - Political organizations protest against violent breaking up of peaceful demonstration in Prague - Visit of US Congress delegation to primarily discuss forthcoming elections - György FejtiI talks in Tata about disagreements within the Party - Hungarian Democratic Forum (MDF) also supports earlier elections Külpolitika: - Tudósítások a szovjet-német meg-nem támadási szerződés évfordulója kapcsán - Tallinni jelentés az élőláncról - Ceauşescu interjú a moszkvai Pravdában - A lengyel parlamentben támogatják Mazowieckit Belpolitika: - Politikai szervezetek tiltakozása a békés prágai tüntetés erőszakos feloszlatása ellen - Az Egyesült Államok kongresszusi küldötteinek látogatása, akik elsősorban a következő választásokról tájékozódtak - Fejti György a párton belüli nézeteltérésekről beszélt Tatán - Az MDF is az előrehozott választások mellett van